Multiobjective Thermoeconomic Optimization of the LNG Cold Utilized Micro-cogeneration System - Kanbur, Baris Burak (2018)
Liquefied natural gas (LNG) cold utilization systems are feasible options for the inland and stranded regions where the conventional pipeline technology is challenging. For the best operation conditions of the systems in the real engineering applications, the optimization is a significant step after the design and analysis steps. This study aims to optimize an LNG cold utilized micro-cogeneration system by using the multiobjective optimization strategy with the genetic algorithm. Thermodynamic and thermoeconomic investigations are performed, and then the multiobjective optimization study is carried out according to the net generated power rate, exergetic efficiency, and the levelized product cost as multiobjectives. The study is conducted between 288.15 K and 313.15 K, and the optimum operation conditions are detected between 301.0 K and 302.5 K with respect to the different relative humidities.